2017
DOI: 10.1186/s40168-017-0293-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential and active functions in the gut microbiota of a healthy human cohort

Abstract: BackgroundThe study of the gut microbiota (GM) is rapidly moving towards its functional characterization by means of shotgun meta-omics. In this context, there is still no consensus on which microbial functions are consistently and constitutively expressed in the human gut in physiological conditions. Here, we selected a cohort of 15 healthy subjects from a native and highly monitored Sardinian population and analyzed their GMs using shotgun metaproteomics, with the aim of investigating GM functions actually e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 68 publications
14
120
1
1
Order By: Relevance
“…In Proteobacteria , Pseudomonas , Parasuterella , Haemophilus , Bilophila , Escherichia and Desulfovibrio were the highest contributors to protein group abundances. Our results are in agreement and further extend previous reports on the phylogenetic diversity of microbial proteins within the human gut (Klaassens et al ., ; Verberkmoes et al ., ; Rooijers et al ., ; Kolmeder et al ., ; Ferrer et al ., ; Perez‐Cobas et al ., ; Juste et al ., ; Brooks et al ., ; Kolmeder et al ., ; Tanca et al ., ; Zwittink et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…In Proteobacteria , Pseudomonas , Parasuterella , Haemophilus , Bilophila , Escherichia and Desulfovibrio were the highest contributors to protein group abundances. Our results are in agreement and further extend previous reports on the phylogenetic diversity of microbial proteins within the human gut (Klaassens et al ., ; Verberkmoes et al ., ; Rooijers et al ., ; Kolmeder et al ., ; Ferrer et al ., ; Perez‐Cobas et al ., ; Juste et al ., ; Brooks et al ., ; Kolmeder et al ., ; Tanca et al ., ; Zwittink et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…[20] A previous study has assessed the interaction between atypical antipsychotic (AAP) and gut microbiota in BD patients, and showed gender-specific reduction of species richness in AAPtreated females, which may be associated with metabolic factors. [21,22] Butyrate, one of the main products of colonized microbiota, serves as a major energy source for colonocytes, [23] and plays an important role in immune accommodation, gut barrier regulation, gut metabolism, and energy modulation. Phylum Firmicutes were more abundant in healthy individuals, while greater amounts of Bacteroidetes were found in untreated depressed BD patients, in accordance with a previous study in MDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Our results demonstrated that the microbial composition in depressed BD patients was clearly different from HCs. [22,24] Butyrate has been reported to be beneficial for many systemic disorders, such as hemoglobinopathy, genetic metabolic diseases, hypercholesterolemia, insulin resistance, and ischemic stroke. [20] Of note, compared to HCs, decreased abundance of various butyrate-producing bacteria was found in untreated BD patients, including genera Roseburia, Faecalibacterium, and Coprococcus.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a “cell shaving proteomic” approach was used to identify 261 cell surface‐associated proteins of G. vaginalis in culture . This technology has several advantages as the metaproteome reflects the actual protein output, which may diverge from measures of bacterial community structure defined by amplicon sequencing, gene content (SMS) or metatranscriptomes .…”
Section: Introductionmentioning
confidence: 99%